First record of the black soldier fly,Hermetia illucens, in Greece - Tsagkarakis, Antonios E; Arapostathi, E. I.; Strouvalis, G. I. (ENTOMOLOGIA HELLENICA, 2015)
In May 2015, the black soldier fly Hermetia illucens (L.) (Diptera: Stratiomyidae) was recorded for the first time in Greece. Its occurrence was noticed firstly in May 2015 in the island of Naxos, Cyclades. Newly hatched larvae of H. illucens feed on different decaying organic material, such as rotting fruits and vegetables, animal manure and human excreta, achieving a significant dry mass reduction. Thus, they are considered to provide remarkable ecological service on recycling. Information on its morphology, biology and distribution is given.